2003
DOI: 10.2113/geoarabia080109
|View full text |Cite
|
Sign up to set email alerts
|

Tilted original oil/water contact in the Arab-D reservoir, Ghawar field, Saudi Arabia

Abstract: A review of the electrical logs, fluid properties, and production history of 195 flank wells drilled in the Arab-D carbonate reservoir of the Ghawar field, Saudi Arabia, showed that the original oil/water contact was regionally tilted. The contact was about 200 ft higher in the southern Haradh sector than in the northern Shedgum and ‘Ain Dar sectors. In Haradh, the fluid contact was also locally tilted down from west to east by as much as 800 ft. In the reservoir, the oil and aquifer densities changed from lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…It is likely that these self-flowing oil wells will be able to provide the fuel for ships during the catastrophe recovery. For example, although the Saudi Ghawar oil field now uses active water injection to maintain positive pressure, it is likely that the oil field will still produce oil for the duration of the recovery [40]. Furthermore, the fuel requirement of ships can be reduced or completely replaced by next-generation wind technology, which uses paragliding sails [41,42], which plausibly could be produced in this loss of industry scenario.…”
Section: Food Transportationmentioning
confidence: 99%
“…It is likely that these self-flowing oil wells will be able to provide the fuel for ships during the catastrophe recovery. For example, although the Saudi Ghawar oil field now uses active water injection to maintain positive pressure, it is likely that the oil field will still produce oil for the duration of the recovery [40]. Furthermore, the fuel requirement of ships can be reduced or completely replaced by next-generation wind technology, which uses paragliding sails [41,42], which plausibly could be produced in this loss of industry scenario.…”
Section: Food Transportationmentioning
confidence: 99%
“…In a similar vein, Dashash et al [81] reported a successful water shutoff task in a horizontal producer in the South Ghawar field completed as an open-hole. All water was produced from the well's toe, according to a PLT run [82]. To separate the area where the water is produced, they utilized inflatable packers in their design.…”
Section: Page|20mentioning
confidence: 99%